Endophytes: The Second Layer of Plant Defense. (April 2020) - Dini-Andreote, Francisco
Abstract : Microorganisms in association with roots can protect plants against soil-borne diseases. A recent study mechanistically revealed how root endophytes act as a second microbiological layer of plant defense. Integrating ecological concepts with principles of plant pathology provides an innovative way to manipulate and engineer beneficial plant microbiomes.